Chemoprophylaxis of Shigella flexneri Keratoconjunctivitis in Rabbits - Cross, W. R. (1970)
Chloramphenicol, chlortetracycline, streptomycin, and sulfisoxazole prevented keratoconjunctivitis in rabbit eyes infected with Shigella flexneri. The route of administration of the agent and the dose were important variables in controlling the infectious process. This assay system appears to be a useful technique for the in vivo evaluation of chemotherapeutic agents.